Police’s Role to Prevent Criminal Act of Rape-Murder (Study Case of Police Labuhan Ruku Talawi Sub-District, Batubara District, North Sumatera) - Rizkan Zulyadi (Budapest International Research and Critics University, 2020)
This study aims to analyze how the factors causing the occurrence of criminal act of rape-murder, what is the role of investigators in uncovering criminal act of rape-murder police of Batubara District, What are the obstacles faced by investigators in uncovering rape-murder in Police Labuhan Ruku Talawi. The research method uses in this study is Analytical Descriptive. In this case the researchers directly conducted research into Police Labuhan Ruku Talawi, Batubara Sub-District, North Sumatera. The results shows obtained are criminal acts of murder can occur due to factors that support the occurrence of these killings which can be caused through many things including through, conditions, circumstances and so forth that give room for the occurrence of these things. The role of the police investigator is to uncover the occurrence of a criminal act of murder through a series of acts of search and examination of matters relating to the murder case. Obstacles faced by investigators in uncovering murder cases include the lack of equipment and facilities and also the absence of witnesses that complicate the examination process.